Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis. Issue 6 (19th March 2023) - Cavalcanti, Andreza Barbosa Silva; Maia, Mayara dos Santos; Figueiredo, Pedro Thiago Ramalho de; Menezes, Renata Priscila Barros de; Monteiro, Alex France Messias; Meireles, Roseana Araújo Ramos; Rodrigues, Gabriela Cristina Soares; Rodrigues de Almeida Silva, Ana Rita; Lins, Jociano da Silva; Cordeiro, Laísa Vilar; Junior, Valnês S. Rodrigues; Castelo Branco, Ana Paula O. T.; et al.
Abstract: Plants of Hyptidinae subtribe (Lamiaceae – family), as Mesosphaerum sidifolium, are a source of bioactive molecules. In the search for new drug candidates, we perform chemical characterization of diterpenes isolated from the aerial parts of M. sidifolium was carried out with uni- and bidimensional NMR spectral data, and evaluate in silico through the construction of a predictive model followed by in vitro testing Mycobacterium tuberculosis and Mycobacterium smegmatis . Resulted in the isolation of four components: Pomiferin D (1), Salviol (2), Pomiferin E (3) and 2α-hydroxysugiol (4), as well as two phenolic compounds, rosmarinic and caffeic acids. In silico model identified 48 diterpenes likely to have biological activity against M. tuberculosis . The diterpenes isolated were tested in vitro against M. tuberculosis demonstrating MIC = 125 µM for 4 and 1, while 2 and 3 -MIC = 250 µM. These compounds did not show biological activity at these concentrations for M. smegmatis . Graphical Abstract: UF0001